Changes in body composition and blood pressure in students entering in university education: a 32-month longitudinal study - Paulo, Rui (2021)
The university access entails some constraints on the lifestyles of young students, including their physical activity patterns. This study objective to know if the students who entered university education and who attend courses in sports sciences have more adjusted values in terms of body composition and blood pressure in relation to students taking other courses. METHODS: Thirty-one students (age 19.81±1.64 years) participated in this study, of both sexes, divided in two groups: sports students group (N.=19); and students group from other courses (N.=12). Body composition was evaluated, namely Body Mass Index (BMI), waist circumference (WC), hip circumference (HC), using tetrapolar bio impedance (Tanita BC-601) the percentage of body fat (%BF), muscle mass (MM) and bone mineral (BM) were calculated. Blood pressure (SBP/DBP) was also measured (Omron DBP HEM-907). We checked the distribution of the sample. For the variables with normal distribution, we used the paired t-test and for the other variables with non-normal distribution we used the Wilcoxon test. Comparing baseline and follow-up, in sports students, there are differences for the variables WC, HC, MM, BM and SBP. In these comparisons, there was an increase in the absolute values of all variables, except for the %BF, SBP and DBP variables. The group of students from other courses, presents differences for the BMI, WC, HC, %BF and DBP. Students from the Sports course present better overall results in terms of body composition and blood pressure, compared to students from other courses.